1952
DOI: 10.1099/00221287-7-3-4-295
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Antibiotics in Soils

Abstract: SUMMARY:Ten antibiotics have been included in this study : eight of them were metabolic products of fungi isolated from soils of the Bagshot Sand type. Their stability in Bagshot Sand soils and in a neutral garden loam has been investigated. Some were more stable than others, the rate of inactivation varied from soil to soil, but all exhibited a fair degree of stability in some of the soils. Four types of inactivation could be distinguished: (1) The natural pH of the soil was sometimes that at which the antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1956
1956
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…It has been concluded that although soil colloids adsorb antibiotics, they may not be totally inactivated and the adsorption can be reversible [31][32][33][34]. Soil conditions can also affect the amount of streptomycin that is bound, for example, particulate matter can bind more streptomycin under acid conditions [35]. For the type of sop used in our experiments the results support the conclusion that streptomycin can be active in soil.…”
Section: Salmonella Sensitivity To Streptomycin In Soilsupporting
confidence: 83%
“…It has been concluded that although soil colloids adsorb antibiotics, they may not be totally inactivated and the adsorption can be reversible [31][32][33][34]. Soil conditions can also affect the amount of streptomycin that is bound, for example, particulate matter can bind more streptomycin under acid conditions [35]. For the type of sop used in our experiments the results support the conclusion that streptomycin can be active in soil.…”
Section: Salmonella Sensitivity To Streptomycin In Soilsupporting
confidence: 83%
“…Mineral adsorption of streptomycin was found to be enhanced as pH declined from neutral to acidic conditions, thereby affecting its antibiotic activity [86]. This issue, however, can be resolved by adjusting antibiotic doses applied to individual soils.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…A well-known source of microbial degradation activities is soil. Biological degradation of mycotoxins griseofulvin, mycophenolic acid and patulin in soil has been reported as early as in 1952 (Jefferys, 1952); however, active mixed cultures from soil often lose activity after separation into pure cultures, as reported for zearalenone (Megharaj et al, 1997) and DON (He et al, 1992;Binder et al, 1997a).…”
Section: Search For Mycotoxin-transforming Microorganisms: General Comentioning
confidence: 99%